(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out self-regulated learning in mathematics learning. This study uses a quantitative approach with a descriptive method. The SRL scale test of students in mathematics was carried out at a junior high school in the city of Bandar Lampung with a sample of 41 students. This study uses a quantitative approach with a descriptive method. The SRL scale test of students in mathematics was carried out at a junior high school in the city of Bandar Lampung with a sample of 41 students. The questionnaire used to measure SRL has indicators, namely the strategies used by students to learn, motivational strategies for learning, and SRL components. Data analysis was carried out descriptively on the results of student responses on the questionnaire scale used. The results of data analysis showed that the instrument that measured SRL as an overall attitude of students took the initiative in learning mathematics, selected, and applied the right strategy, evaluated the learning process and outcomes, and reflected in learning mathematics